The effect of fillers on the overall migration resistance and mechanical properties of food-grade natural rubber gloves - Sirithorn Kaewklum; Parisa Faibunchan; Apinya Krainoi; Banyat Cherdchim; Jutharat Intapun (eXPRESS Polymer Letters, 2025)
Powder-free natural rubber gloves for chemical migration resistance of food-contact grade are prepared using a variety of fillers, including ground calcium carbonate (GCC), precipitated calcium carbonate (PCC), aluminum silicate (AS), and barium sulfate (BS)-filled natural rubber (NR), respectively. The properties of NR gloves, including mechanical, dynamic mechanical, and thermal properties, were investigated. Furthermore, the overall migration test of NR gloves was conducted according to the regulations for food contact gloves (EU Regulation No. 10/2011), using 3% acetic acid as the simulant. Among the fillers studied, the plate-like particles of AS facilitated the most effective filler-rubber interactions and reinforcement in AS-filled natural rubber (NR/AS). Consequently, the highest crosslink density, force at break, and damping properties of NR gloves were achieved by applying AS in the NR matrix. Moreover, the lowest overall migration level was observed for NR/AS with a value of 5.35 mg/dm2, which complies with EU Regulation (overall migration of food simulants shall not exceed 10 mg/dm2). Therefore, NR gloves filled with AS are suitable for food-contacting NR gloves.